Extending the use of PROMs in the NHS—using the Oxford Knee Score in patients undergoing non-operative management for knee osteoarthritis: a validation study - Harris, K; Dawson, J; Jones, L; Beard, D; Price, A (BMJ Publishing Group, 2013)
OBJECTIVES: To assess the validity of the Oxford Knee Score (OKS) for use in patients undergoing non-operative management for their knee osteoarthritis (OA) within the National Health Service (NHS). DESIGN: Observational cohort study. SETTING: Single orthopaedic centre in England. PARTICIPANTS: 134 patients undergoing non-operative management for knee OA. MAIN OUTCOME MEASURES: OKS, the Intermittent and Constant Osteoarthritis Pain (ICOAP), the Knee Injury and Osteoarthritis Score-Physical Function Short Form (KOOS-PS), at baseline and 3-month follow-up, transition item of change at 3 months. RESULTS: The OKS summary scale and its pain and functional component subscales demonstrated good test-retest reliability (intraclass correlation coefficient 0.93, 0.91 and 0.92, respectively) and measurement precision which, allows its use with groups of patients with knee OA (research/audit) and with individuals (clinical practice). The results in this study were consistent with a priori set hypotheses about the relationship of OKS with other validated measures (KOOS-PS, ICOAP and short form 12 (SF-12)), which provided evidence of its construct validity and responsiveness. Confirmatory factor analysis confirmed the structural validity of OKS. However, there was a lack of satisfactory evidence of structural validity for ICOAP and KOOS. The minimum detectable change (MDC90) was ±6 for OKS (±16 for the Pain Component Score (OKS-PCS) and ±15 for the Functional Component Score (OKS-FCS)). Minimal important changes were ≈7 for OKS (≈17 for OKS-PCS and ≈11 for OKS-FCS) and minimal important differences were ≈6 for OKS (≈14 for OKS-PCS and ≈10 for OKS-FCS). These values were also calculated for ICOAP and KOOS-PS. CONCLUSIONS: The OKS summary scale, together with its pain and functional component subscales, has excellent measurement properties when used with patients with knee OA undergoing non-operative treatment and is superior to ICOAP and KOOS-PS for this purpose. This evidence provides support for the validity of the use of OKS when used across the spectrum of knee OA disease severity, both in research and clinical practice.